Friction and Mechanical Properties of AFM-Scan-Induced Ripples in Polymer Films - Friedrich, Sebastian; Cappella, Brunero (Frontiers in Mechanical Engineering, 2021)
When compliant samples such as polymer films are scanned with an atomic force microscope (AFM) in contact mode, a periodic ripple pattern can be induced on the sample. In the present paper, friction and mechanical properties of such ripple structures on films of polystyrene (PS) and poly-n-(butyl methacrylate) (PnBMA) are investigated. Force volume measurements allow a quantitative analysis of the elastic moduli with nanometer resolution, showing a contrast in mechanical response between bundles and troughs. Additionally, analysis of the lateral cantilever deflection when scanning on pre-machined ripples shows a clear correlation between friction and the sample topography. Those results support the theory of crack propagation and the formation of voids as a mechanism responsible for the formation of ripples. This paper also shows the limits of the presented measuring methods for soft, compliant, and small structures. Special care must be taken to ensure that the analysis is not affected by artefacts.